Magnetically Guided Capsule Endoscopy and Magnetic Resonance Enterography in Children With Crohn’s Disease: Manifestations and the Value of Assessing Disease Activity - Li, Jia; Zhao, Xuesong; Su, Wen; Shen, Ruizhe; Xiao, Yuan; Wang, Xinqiong; Xu, Xu; Xu, Chundi; Li, Na; Yu, Yi (Frontiers in Pharmacology, 2022)
OBJECTIVE To investigate the value of magnetically guided capsule endoscopy (MGCE) and magnetic resonance enterography (MRE) in assessing the activity of pediatric Crohn’s disease. METHODS Clinical data from 82 subjects with pediatric Crohn’s disease, who underwent MGCE and MRE from October 2018 to March 2021 were analyzed retrospectively. Pairwise comparisons of several indexes, including MaRIA, CECDAI, PCDAI, and SES-CD, were performed by Spearman’s rank correlation test and kappa consistency analysis. CECDAI and MaRIA values predicted whether patients were moderately or severely active (PCDAI ≥30) clinically by logistic regression analysis. The area under the receiver operating characteristic curve (AUC) quantified the evaluation value of moderate to severe activity of pediatric CD. RESULTS In judging the severity of CD in the small intestine, the correlation coefficient between CECDAI and MaRIA was 0.406 (P<0.05), and the kappa value of the consistency analysis was 0.299 (P<0.05). MaRIA was weakly correlated with PCDAI (r=0.254, P<0.05), and they were weakly consistent in assessing the activity of Crohn’s disease (kappa=0.135, P<0.05). For predicting clinically moderate to severe activity, the fitted AUC based on CECDAI and MarRIA was 0.917, which was higher than applying a single parameter (CECDAI=0.725, MarRIA=0.899, respectively). MaRIA and serum albumin were significantly and negatively correlated (r=-1.064, P<0.05). The consistency of the detection rate of gastric ulcers by MGCE and gastroscopy was moderate (kappa=0.586, P<0.05), and the detection rate of ulcers in the terminal ileum between MGCE and colonoscopy showed high consistency (kappa=0.609, P<0.05). CONCLUSIONS MGCE and MRE are valuable, non-invasive methods for evaluating small bowel lesions in children with CD. The combined application of MGCE and MRE can better characterize the disease activity.